2020
DOI: 10.1021/acscatal.0c03978
|View full text |Cite
|
Sign up to set email alerts
|

Charge Distribution in Cationic Molybdenum Imido Alkylidene N-Heterocyclic Carbene Complexes: A Combined X-ray, XAS, XES, DFT, Mössbauer, and Catalysis Approach

Abstract: The charge delocalization between the N-heterocyclic carbene (NHC) and the metal in cationic molybdenum imido alkylidene NHC mono(nonafluoro-tert-butoxide) complexes has been studied for different NHCs, i.e., 1,3-dimesitylimidazol-2ylidene (IMes), 1,3-dimesityl-4,5-dichloroimidazol-2-ylidene (IM-esCl 2 ), 1,3-dimesityl-4,5-dimethylimidazol-2-ylidene (IMesMe 2 ), and 1,3-dimesityl-4,5-dihydroimidazol-2-ylidene (IMesH 2 ). The binding situation in the corresponding cationic complexes Mo(N-2,6-Me 2 C 6 H 3 )(CHCM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

7
0

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 57 publications
4
37
0
Order By: Relevance
“…A change in the electronic structure or oxidation state by immobilization in the COF can thus be excluded Results of extended X-ray absorption fine structure (EXAFS) analysis, probing the local geometric structure around an X-ray absorbing atom of the Ru catalyst under homogeneous and immobilized conditions are shown in Figure 4, b. [20] The corresponding first shell scattering paths combined with coordination numbers, bond distances and Debye-Waller factors, which describe the static and dynamic disorder in the coordination shell, are collected in Figure S16 and Table S7. The results of the structure analysis for all samples are in good…”
Section: Resultsmentioning
confidence: 99%
“…A change in the electronic structure or oxidation state by immobilization in the COF can thus be excluded Results of extended X-ray absorption fine structure (EXAFS) analysis, probing the local geometric structure around an X-ray absorbing atom of the Ru catalyst under homogeneous and immobilized conditions are shown in Figure 4, b. [20] The corresponding first shell scattering paths combined with coordination numbers, bond distances and Debye-Waller factors, which describe the static and dynamic disorder in the coordination shell, are collected in Figure S16 and Table S7. The results of the structure analysis for all samples are in good…”
Section: Resultsmentioning
confidence: 99%
“…Oskam and Schrock also found that the less electron-withdrawing the alkoxide ligand is, the faster the rate of interconversion. As the NHC ligand in 1 is a sigma-donor that effectively stabilizes the positive charge of Mo by donating an electron, 12 it can be assumed that the rate of syn – anti interconversion is of similar rate or faster than metathesis.…”
Section: Discussionmentioning
confidence: 99%
“…In general, all NHCÀ W bond lengths are shorter than in their neural precursors, which can be attributed to a delocalization of the positive charge by the NHC. [7] In the same way, the alkoxide ligands are more tightly bound to the cationic metal centers, which is reflected in bond distances of only between 185.0 and 194.2 Å, whereas in the neutral complexes those are mostly > 200 Å. The alkylidene-W and W-oxo bond distances, on the contrary, do not significantly differ from those observed in neutral W oxo alkylidene NHC complexes.…”
Section: Chemcatchemmentioning
confidence: 96%
“…In earlier studies, this strategy was successfully utilized for the correlation of charge distribution and reactivity of cationic molybdenum imido alkylidene NHC complexes. [7] The kinetic profiles as well as TONs, E/Z-selectivity and reaction conditions are available from the Supporting Information. In addition to that, the turnover frequencies after 1 and 3 min (TOF 1min and TOF 3min ) were determined as average of three independent measurements.…”
Section: Chemcatchemmentioning
confidence: 99%
See 1 more Smart Citation